Insurance Perspective of Yusuf Qardhawi and Abdul Wahab Khalaf - Ainul Mardhiah; Afrizal Afrizal (Green Publisher Indonesia, 2021)
Insurance that has just emerged at this contemporary stage, its quality causes mixed understanding among researchers. There are several researchers who prohibit insurance, including Yusuf al-Qardawi who blocks existing insurance, especially life insurance. Yusuf al-Qardawi forbade insurance on the grounds that according to him insurance is far from the idea of exchange and solidarity with the association. Whereas in life insurance, basically it is very possible to say that it is a broken understanding. The explanation is because between the two meetings there is a common desire and currently realizes that the strengths of each are not solid. Insurance in Yusuf al-Qardawi's view is that Islam does not recognize the current type of insurance with every implementation, it does not mean that Islam is against insurance as a whole, not in any way, what Islam opposes is part of its implementation practice. According to Abdul Wahaf Khalaf, insurance takes any form and can benefit the local community as long as there is no usury, the law is halal or allowed in Islamic teachings.